2018
DOI: 10.4314/njt.v37i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of relative humidity on tensile and compressive creep of concrete amended with ground granulated blast-furnace slag

Abstract: This paper presents an experimental study on the influence of ambient relative humidity on tensile creep of plain concrete amended with Ground Granulated Blast-furnace Slag and compares it with its influence on compressive creep. Tensile and compressive creep tests were carried out on concrete specimens of 34.49MPa compressive strength and 0.56 water/binder ratio at 51, 68 and 100% relative humidity. The results show a linear relationship between compressive creep and relative humidity; this cannot be said abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several materials have already been incorporated into concrete production in practice. These include materials like fly ash (Fasihihour et al, 2022), ground granulated blast furnace slag (GGBS) (Ogirigbo and Black, 2017;Ogirigbo and Inerhuwa, 2017;Ambrose and Forth, 2018), silica fumes (Mehta et al, 2020), recycled concrete (Kisku et al, 2017), quarry sand (Verma et al, 2020; and others. Research has confirmed the feasibility of incorporating even many more waste materials.…”
mentioning
confidence: 99%
“…Several materials have already been incorporated into concrete production in practice. These include materials like fly ash (Fasihihour et al, 2022), ground granulated blast furnace slag (GGBS) (Ogirigbo and Black, 2017;Ogirigbo and Inerhuwa, 2017;Ambrose and Forth, 2018), silica fumes (Mehta et al, 2020), recycled concrete (Kisku et al, 2017), quarry sand (Verma et al, 2020; and others. Research has confirmed the feasibility of incorporating even many more waste materials.…”
mentioning
confidence: 99%
“…This has made concrete the most consumed construction material and is simply due to its versatility and sustainability and the fact that concrete constituents can almost always be locally sourced. As put by Ambrose and Forth (2018), concrete is basically, a series of aggregates bonded together by hardened cement paste which is a product of hydration of cement. As such, aggregate usually occupies at least 75% of a typical concrete mix.…”
mentioning
confidence: 99%